Long non-coding RNA LOC283070 mediates the transition of LNCaP cells into androgen-independent cells possibly via CAMK1D - Wang, Lina (Am J Transl Res, 2016)
Aims: The present study is to investigate the role of long non-coding RNAs (lncRNAs) in the development of androgen independence in prostate cancer and its underlying mechanism. Methods: We established an androgen-independent prostate carcinoma (AIPC) cell line LNCaP-AI from androgen-dependent prostate carcinoma (ADPC) cell line LNCaP. Different expression profiles of lncRNAs and mRNAs between LNCaP and LNCaP-AI cells were investigated using microarray analysis. The expression of RNAs was determined using quantitative real-time polymerase chain reaction. Protein levels were measured using Western blotting. MTT assay was used to test cell viability. Tumor formation assay was performed in nude mice to detect tumor growth in vivo. Flow cytometry was performed to detect cell cycles. Transwell assay was employed to test cell migration and invasion. Results: According to bioinformatics prediction, lncRNA LOC283070 could possibly play an important role in the transition of LNCaP cells into LNCaP-AI cells. LOC283070 was up-regulated in LNCaP-AI cells and frequently up-regulated in AIPC cell lines. Overexpression of LOC283070 in LNCaP cells accelerated cell proliferation and migration, even under androgen-independent circumstances. Knockdown of LOC283070 inhibited LNCaP-AI cell proliferation and migration. Moreover, overexpression of LOC283070 promoted tumor growth in vivo in both normal mice and castrated mice. CAMK1D overexpression had similar effect with LOC283070, and CAMK1D knockdown fully abrogated the effect of LOC283070 overexpression on the transition of LNCaP cells into androgen-independent cells. Conclusions: The present study shows that overexpression of LOC283070 mediates the transition of LNCaP cells into androgen-independent LNCaP-AI cells possibly via CAMK1D.